Penilaian Perkhidmatan Dan Kemudahan Kerajaan Tempatan Untuk Peniaga Kecil Di Bandar Bentong, Pahang. - Selvan, Krishnaveni Tamil (2010)

(untitled)
Local authorities play an important role in urban development. Urbanization and development that occur simultaneously and drastically created many challenges to the local authorities in providing services and facilities especially for the small scale traders in the city. The provision of business spaces, trading licenses and permits are very important in determining the direction and role of small scale traders in the economic market in future. An evaluation of a local authority’s services and facilities for small scale traders in the city can help the local government in planning, managing and improving the services and facilities provided to facilitate the local economic development. In addition, this study also aims to investigate the effectiveness and the strategies used by the local authority, particularly the Bentong Municipal Council (MPB), in providing services and facilities to small scale traders in the study area. Quantitative and qualitative analyse have been done towards the information and data obtained from primary and secondary sources, through survey questionnaires and interviews with MPB officers as well as community leaders. Findings from this research showed that there were some problems faced by the small scale traders in regards to the services and facilities provided by the MPB. Among the problems are design of the stalls, limited stall area, insufficient car parking lots, water supply and others. Few suggestions have been recommended for the MPB to improve the quality of its services. This study hopes to contribute useful information in these issues and become the pioneer for future studies. Although small scale traders are just a small component in the function and development of the city, the role of local authorities in providing services and facilities for the traders in achieving socioeconomic development is very vital.